2016
DOI: 10.1136/jclinpath-2015-203397
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic values of ERCC1 and XRCC1 in biliary tract cancers

Abstract: IHC expression of ERCC1 and XRCC1 has some predictive and prognostic values in patients with BTC. Nuclear expression of ERCC1 and XRCC1 may be used to predict therapeutic response in patients undergoing gemcitabine monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Thus, we further evaluated the clinicopathological and prognostic significance of XRCC1 in gallbladder SC/ASC and AC. Our data demonstrated that XRCC1 positive expression was significantly related to lymph node metastasis, invasion, and poor prognosis, which was consistent with previous studies (Ang et al, 2011;Abdel-Fatah et al, 2013;Mian et al, 2016). Moreover, cox univariate and multivariate analysis further showed that XRCC1 positive expression was an independent risk factor for the FIGURE 3 | XRCC1 has no effect on proliferation, migration, invasion, and apoptosis of CD133 + GBC-SD cells.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we further evaluated the clinicopathological and prognostic significance of XRCC1 in gallbladder SC/ASC and AC. Our data demonstrated that XRCC1 positive expression was significantly related to lymph node metastasis, invasion, and poor prognosis, which was consistent with previous studies (Ang et al, 2011;Abdel-Fatah et al, 2013;Mian et al, 2016). Moreover, cox univariate and multivariate analysis further showed that XRCC1 positive expression was an independent risk factor for the FIGURE 3 | XRCC1 has no effect on proliferation, migration, invasion, and apoptosis of CD133 + GBC-SD cells.…”
Section: Discussionsupporting
confidence: 91%
“…A recent publication showed that vascular invasion was significantly more frequent in patients with biliary tract cancers with a low expression of XRCC1 [ 15 ]. Metastasis of ccRCC cells remains the major cause of mortality in patients with ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have also explored the potential predictive impact of excision repair cross-complementation group 1 (ERCC1) and X-ray repair cross-complementing group 1 (XRCC1) in tumor samples from patients with GBC (and other BTCs) undergoing gemcitabine as adjuvant therapy [129]. This study showed that high nuclear expression of both proteins was able to predict better overall survival [129].…”
Section: Predictors Of Response To Adjuvant Treatmentmentioning
confidence: 99%